Mapping of aeolian deposits of an industrial site in the arid region using the TIR bands of ASTER and study of physicochemical characters and stabilization of sand erosion - Rajendran Sankaran (13790375) (2022)
This study describes the spectral emissive character of silicate and carbonate minerals of aeolian deposits and maps the deposits and sand encroachments that occurred in and around the site 5/6 of Qatar Fertilizer Company (QAFCO), Qatar using thermal infrared (TIR) bands of ASTER. The results of studies show that the quartz and unaltered silicates have spectral features between 8.12 and 9.27 µm, and the calcite and dolomite have emissivity minima near 11.4 and 11.2 µm, respectively. The mapping of deposits, dunes, and carbonate formations using the bands, and quartz index (QI), and carbonate index (CI) displayed their occurrence, distribution, and direction of sand movement from NW to SE. The sand encroachment was mapped using high spatial resolution satellite data of WorldView-2. The study of physicochemical characteristics of field samples showed the occurrence of sand grains up to 99.81% and the XRD and geochemical analyses represented the presence of quartz, calcite, dolomite, albite, and halite minerals in the deposits. In addition, the bacterial strains isolated from the samples indicated high urease activity leading to precipitation of carbonate minerals via microbially induced calcite precipitation (MICP) processes, and demonstrated high potential for utilization for sand stabilization of the QAFCO site. Other Information Published in: Geomatics, Natural Hazards and Risk License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/19475705.2022.2122873